Pemanfaatan Limbah Fiber Ex-Fibercyclone dan Tandan Kosong Kelapa Sawit sebagai Bioetanol dengan Menggunakan Bakteri Zymomonas mobilis - Indriana Lestari (JURNAL CITRA WIDYA EDUKASI, 2019)
Ethanol made from berlignocellulose biomass is a technology for producing fuel as a new renewable energy source (NRE) that is sustainable, environmentally friendly and does not compete with foodstuffs. Fiber ex-fibercyclone and empty bunch is a lignocellulose material produced by palm oil mill with a large volume. Research on the manufacture of bioethanol from ex-fibercyclone and empty oil palm fiber using Zymomonas mobilis bacteria was carried out. The purpose of this study was to determine the potential of fiber ex-fibercyclone and empty bunch solid wastes as ethanol feedstock and optimal fermentation time to obtain the highest ethanol production. The waste samples went through 3 stages of the process, namely delignification using 4% NaOH, followed by hydrolysis using 2% H2SO4 and hydrolyzate fermentation using Zymomonas mobilis which was carried out for 3, 4, 5 and 6 days. The fermentation result were analyzed using a refractometer and GC-FID. The results showed that fiber ex-fibercyclone and empty bunch solid waste had the potential to be made bioethanol using Zymomonas mobilis bacteria with optimal fermentation time for 4 days and obtained ethanol yield from ex-fibercyclone fiber by 60% (v/b) and 82% (v/b) of empty bunch, while ethanol level measured by GC-FID were 0.0346% and 1.886%, respectively. The empty bunch waste produces more ethanol than ex-fibercyclone fiber.